Choosing Wisely in pediatric healthcare: A narrative review - Trapani, Sandra; Montemaggi, Alessandra; Indolfi, Giuseppe (Frontiers in Pediatrics, 2023)
Background: It has been estimated that 20% of the tests and therapies currently prescribed in North America are likely unnecessary, add no value, and may even cause harm. The Choosing Wisely (CW) campaign was launched in 2012 in the US and Canada to limit the overuse of medical procedures in adult and pediatric healthcare, to avoid overdiagnosis and overtreatment. Methods: In this narrative review, we describe the birth and spread of the CW campaign all over the world, with emphasis on CW in pediatric healthcare. Results: To date, CW has spread to more than 25 countries and 80 organizations, with 700 recommendations published. The awareness of medication overuse also made its way into pediatrics. One year after the launch of the CW campaign, the American Academy of Pediatrics and the pediatric section of the Society of Hospital Medicine provided the first recommendations aimed explicitly at pediatricians. Thereafter, many European pediatric societies also became active in the CW campaign and published specific top-5 recommendations, although there is not yet a common set of CW recommendations in Europe. Discussion: We reviewed the main pediatric CW recommendations in medical and surgical fields and discussed how the recommendations have been produced, published, and disseminated. We also analyzed whether and how the CW recommendations impacted pediatric medical practice. Furthermore, we highlighted the common obstacles in applying CW recommendations, such as pressure from patients and families, diagnostic uncertainty, and worries about legal problems. Finally, we highlighted the necessity to foster the CW culture, develop an implementation plan, and measure the results in terms of overuse decline.